Pendekatan Sejarah Dalam Hukum Wakaf Imam Hanafi - Laila Afni Rambe; Sitta 'Ala Arkham (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
Historical approach is a method used in analyzing a problem. In this paper the historical approach is used to look at the factors that influence the opinion of Imam Hanafi on the position of ownership of waqf property. According to the opinion of Imam Hanafi when a waqf endows his property, it does not make the transfer of ownership of the waqf property. Until the endowment property still belongs to a wakif even though the property has been endowed. After a study, it was concluded that Imam Hanafi's opinion was influenced by his past history as a trader. In addition, the State of Iraq, where he lived, was far from the source of hadith in the time of the Prophet, so Imam Hanafi was more dominant in using Ra'yu in viewing and establishing the law on an event that occurred.